Removal and Preconcentration of Pb(II), V(V), Cr(VI) from the Aqueous Solution and Selective Separation of V(V)-Cr(VI) by Using Functionalized Amberlite XAD-16 Resin with Dithioethylenediamine - Dolak, Ibrahim; Tegin, Ibrahim; Guzel, Remziye; Ziyadanogullari, Recep (Asian Journal of Chemistry, 2010)
Amberlit XAD-16 was functionalized using dithioethylenediamine as a ligand and characterized by elemental analysis and FTIR spectroscopy. The effects of contact time, pH, electrolyte and the concentration of eluents on separation and preconcentration of Pb(II), Cr(VI) and V(V) were studied. In addition, the batch capacity for each ion was determined under the optimum conditions. The preconcentration yields of Pb(II), Cr(VI) and V(V) were found to be 96.60 ± 3.02, 100.64 ± 2.24 and 98.20 ± 3.00 %, respectively, with 500 times preconcentration factor under the optimum conditions. The selective separation of Cr(VI)-V(V) was studied in terms of pH. It was determined that V(V) separated in 98.24 ± 1.21 % yield from the solution containing Cr(VI)-V(V) and Cr(VI) remained in the solution at pH 2.5, while Cr(VI) separated in 101.43 ± 3.09 % yield from the solution containing Cr(VI)-V(V) and V(V) remained in the solution at pH 8.5 by using Amberlit XAD-16-dithioethylenediamine -Pb(II).